Cardiovascular changes in the NZB/W F1 mouse model of lupus nephritis - Böhme, Romy; Daniel, Christoph; Ferrazzi, Fulvia; Angeloni, Miriam; Ekici, Arif Bülent; Winkler, Thomas H.; Hilgers, Karl-Friedrich; Wellmann, Ute; Voll, Reinhard E.; Amann, Kerstin (Frontiers in Cardiovascular Medicine, 2023)
Background: Cardiovascular morbidity and mortality is high in patients with the autoimmune disease systemic lupus erythematosus (SLE). In addition, up to 40-50% of SLE patients develop lupus nephritis (LN) and chronic kidney disease, which is an additional cardiovascular risk factor. Thus, the individual contributions of LN and other SLE-specific factors to cardiovascular events are not clear. Methods: In this study, we investigated the effect of LN on the development of cardiovascular changes using the female NZB/W F1 (NZB/W) model of lupus-like disease with female NZW mice as controls. Standard serologic, morphologic, immunohistologic, and molecular analyses were performed. In a separate group of NZB/W mice, systolic blood pressure was measured during the course of the disease using tail plethysmography. Results: Our data show marked cardiovascular changes in NZB/W mice, i.e. increased heart weight, hypertrophy of the left ventricle and septum as well as increased wall thickness of the intramyocardial arteries and the aorta, which correlated with the progression of renal damage but not with the age of the mice. In addition, systolic blood pressure was increased in NZB/W only when kidney damage progressed and proteinuria was present. Pathway analysis based on gene expression data revealed a significant upregulation of the response to interferon beta in NZB/W mice with moderate kidney injury compared to NZB mice. Furthermore, IFI202b and IL-6 mRNA expression correlated with cardiovascular changes. Multiple linear regression analysis demonstrated both serum urea as surrogate marker of kidney function and IFI202b expression as independent predictors for LV wall thickness. In addition, deposition of complement factors CFD and C3c in hearts from NZB/W mice was seen which correlated with the severity of the kidney disease. Conclusions: Thus, we postulate that the pathogenesis of cardiovascular disease in SLE is affected by renal impairment, i.e. lupus nephritis, but it can also be partly influenced by lupus-specific cardiac expression of pro-inflammatory factors and complement deposition.